Dejavniki oblikovanja kolektivne identitete - Iglič, Hajdeja (Teorija in praksa, 2014)
The article discusses the social sources of collective identification. The main goal is to assess the relevance of three different sociological theories of collective identification, namely the theory of collectively possessed knowledge (Shils, 1991), the theory of nested identities (Calhoun, 1994) and the theory of ultimate community (Deutsch, 1966), for understanding the contemporary processes of European identity formation. In accordance with different theoretical frameworks, the empirical analysis of sources of European identification include the variables of social capital as measures of social integration, institutional trust and mobilisation through political networks, and cognitive competence. The results of the study confirm the importance of social networks for the strength of collective identification, and the role of political mobilisation through political parties, movements and discussion networks for selective identification with either immediate or distant collectivities. Cognitive competence theory does not seem to play a role in explaining the variations in the strength of European identification.
Keywords: European identity; European Union; Evropska identiteta; Evropska unija; Identification; Identifikacija; identiteta; Javnopolitična omrežja; Policy networks; Social capital (Sociology); Socialni kapital (Sociologija)